Anticompetitive impact of pseudo-generics - Rodrigues, Vasco (2016)
A puzzling feature of pharmaceuticals markets is that sellers of branded drugs will, sometimes, sell generic versions of their own branded products, either directly or through license agreements. This paper proposes a new theoretical rationale for the fact that the introduction of these pseudo- generics may have anti-competitive e¤ects. In a model that combines horizontal and vertical product di¤erentiation, we show that the producer of the branded product will not sell the pseudo-generic unless faced with competition and that, if she does so, in some circumstances, all prices raise to the bene t of all competitors and the detriment of consumers.